The fabrication of gold nanotubular membranes and their applications in separations - Jirage, Kshama B., author; Martin, C. K., advisor (Colorado State University. Libraries, 1999)
Membrane based template synthesis and an electroless deposition method was used to fabricate Au nanotubular membranes. The inside diameter of the nanotubules was controlled by varying the time of deposition. The final diameters of the nanotubules were on the order of few angstroms, comparable to the size of molecules. It was demonstrated that these membranes show, "molecular sieving" and can completely separate molecules differing in size. Furthermore, the chemical environment of the nanotubules can be controlled by chemisorbing thiols with different terminal groups. Membranes modified with hydrophobic thiols, are selective to hydrophobic molecules and when modified with hydrophilic thiols, the membranes are selective to hydrophilic molecules. In addition, these membranes can separate molecules when present in a mixture. Au nanotubular membranes can be modified by thiols with charged terminal groups. For e.g., membranes modified with -COO- terminated thiol, were cation-permselective. When modified with -NH3+ terminated thiol, the membranes were anion-permselective. Membranes were permselective in a larger range of electrolyte concentrations for large anions. Finally, Au-Polyacrylic acid (PAA) composite was synthesized in a polyester template membrane by the consecutive deposition of Au and PAA. Au was deposited by electroless deposition and PAA wad deposited by vacuum assisted deposition method. This composite can function as a chemical valve, upon change with pH in the presence of buffer. Furthermore, the composite also functions as an electrochemically controlled valve by the generation of H+ and OH- ions at the Au surface.
Keywords: analytical chemistry; materials science